In-house R&D, technology transfer, and firms' performance - Doan Ha Thi Thanh; Long Quang Trinh (Asian Development Bank Institute (ADBI), 2023)
This study examines the individual and joint impact of technology transfer and in-house R&D on firms' productivity and export performance. We utilize a specially designed survey module on firms' technology competitiveness in Vietnamese manufacturing, which allows us to identify various forms of technology transfer directly at firm-level. We find that technology transfer exhibits a positive impact on firms' exports. The estimated coefficients on both export participation (the extensive margin) and export share (the intensive margin) are positive and significant. In terms of productivity, our result suggests the presence of vertical spillover. Technology transfer along the supply chain is associated with higher productivity- the coefficient is strongest in terms of significance level and magnitude. A long-term relationship with business partners along the supply chain can enhance the effectiveness of technology transfer, thus improving productivity. This finding suggests the potential effectiveness of policies to further enhance linkages between upstream and downstream firms, through which technology transfer can be promoted. Other forms of technology transfer, however, do not show robust impact on productivity. With regard to R&D, we find weak evidence of R&D impact. Only estimated coefficients on export participation are significant. Finally, the joint impact of R&D and technology transfer only shows on exports through firms who purchase embodied technology through goods or equipment.
Keywords: O3; F23; 330; research and development; technology transfer; firms' heterogeneity; trade; productivity